ANALISIS PENGARUH PERSEPSI ATAS ORIENTASI PELANGGAN DAN REPUTASI PERUSAHAAN TERHADAP ORIENTASI PELAYANAN STRATEGIK DAN DAMPAKNYA PADA KEPUASAN PELANGGAN - Jatmiko, Robby (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2015)
This research analyzes the effect of perception on customer orientationand perception on company reputation on perception of strategic serviceorientation and its impact on customer satisfaction. The research problem isbased on 2 (two) issues: first is research gap based on previous researchbackground for example, referring to the borders and direction of researchwill come on and inconsistent with previous findings such as in Homburg etal., ( 2002); Chenet et al., (2000); Pelham, (1997); Doney and Cannon(1997). And the second comes from the research problems, which is found inthe data that gives an overview of the condition of PT. MandalatamaArmada Motor deals with the targets and sales realization of "Honda"brand products in Semarang region, where in 2005 PT. MandalatamaArmada Motor can not meet the targeted marketing of 869 units and canonly be realized 725 or 83% only.A model has been developed and five hypotheses have been formulatedto address this research problem. Sampling technique is purposive method(purposive sampling). Respondents from this study amounted to 120respondents, where respondents are customers of PT. Mandalatama ArmadaMotor. The data analysis tool used is Structural Equation Modeling (SEM)in AMOS 4.01 program. The results of this research data analysis show themodel and research results can be received well. And furthermore the resultsof this study prove the influence of perceptions on customer orientation toperceptions of strategic service orientation is a significant positip.Perceptions of a company's reputation have a positive effect on perceptions ofstrategic service orientation. Perceptions of customer orientation have apositive effect on customer satisfaction. And the influence of perceptions onthe company's reputation on customer satisfaction is a significant positively.As well as perceptions of the orientation of strategic services positively affectcustomer satisfaction